The Urgency of Social Problematic as Sex Education Material and Media In PAUD - Gustinah, Ambarsari Utamining; Harun, Harun; Islamiyah, Roudlotul (Jurnal Pendidikan Indonesia, 2020)
This study aims to analyze the influence and relationship as a form of conformity between the application of material and learning media in sex education in Early Childhood Education (PAUD) in child protection efforts. The research sample was 34 teachers in Surabaya who were randomly selected. This research uses an ex post facto quantitative approach with data collection techniques using a questionnaire. The analysis technique uses simple linear regression because this study did not do anything so only wanted to find out whether there is an influence and the relationship between the application and sex education material in learning media in PAUD. The results of this study are tcount> t table and p value (sig) of 0.036 (<0.05) means that Ho is rejected and Ha is not rejected (accepted). Based on the results of this study it can be concluded that there is a significant conformity (13.1%) between the application of material and media, especially about social problems in sex education in early childhood education which is most important and urgent to give to children.